2020
DOI: 10.1088/1748-0221/15/08/p08004
|View full text |Cite
|
Sign up to set email alerts
|

Simulated response of MuTe, a hybrid Muon Telescope

Abstract: In this paper we present a complete and detailed computational model of the response of the hybrid Muon Telescope (MuTe), designed to perform muography volcanic studies. This instrument combines two particle detection techniques: first, a muon hodoscope based on two panels of plastic scintillator bars; and a Water Cherenkov detector located behind the rear scintillator panel acting both as a coincidence and a discriminating detector. The simulation model includes: materials, geometries, dimensions, and the pho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 42 publications
2
19
0
Order By: Relevance
“…Notice that there are regions where the incoming muon flux is absorbed due to the volcano's geometry, and some of the distances travelled could easily exceed 900 meters. The statistics of 100 muons/pixel for the above MuTe configuration is consistent with other more realistic studies ( see references (Vesga-Ramírez et al, 2017;Vásquez-Ramírez et al, 2019b;Peña-Rodríguez et al, 2020;Moss et al, 2018) for further details).…”
Section: Implementing the Inversionsupporting
confidence: 88%
See 2 more Smart Citations
“…Notice that there are regions where the incoming muon flux is absorbed due to the volcano's geometry, and some of the distances travelled could easily exceed 900 meters. The statistics of 100 muons/pixel for the above MuTe configuration is consistent with other more realistic studies ( see references (Vesga-Ramírez et al, 2017;Vásquez-Ramírez et al, 2019b;Peña-Rodríguez et al, 2020;Moss et al, 2018) for further details).…”
Section: Implementing the Inversionsupporting
confidence: 88%
“…In this section, we briefly describe our hybrid Muon Telescope, MuTe, and the selected muography observation site at Cerro Machín in the department of Tolima. Details of the instrument operation and calibration are considered in (Vásquez-Ramírez et al, 2019b;Peña-Rodríguez et al, 2019;Peña-Rodríguez et al, 2020), while the reasons in choosing Cerro Machín among 13 other Colombian volcanoes can be found in reference (Vesga-Ramírez et al, 2017).…”
Section: Muography In Colombiamentioning
confidence: 99%
See 1 more Smart Citation
“…We performed a particle background characterization by means of Monte Carlo simulations by using the CORSIKA code. The results showed that particles reaching the MuTe are mainly positrons/electrons (∼20 MeV average energy), and muons (∼3 GeV average energy) [15].…”
Section: Pos(ichep2020)984mentioning
confidence: 99%
“…We carried out simulations using the particle-matter interaction code GEANT4 to characterize the mean incident photon signal on the PMT cathode generated by charged particles crossing the WCD. We injected 10 5 muons of 3 GeV perpendicularly to a 120 cm height WCD [17], [18]. The average number of Cherenkov photons (N γ ) along the path were 46857, 1617 of such photons reach the PMT optical window and the PMT photocathode releases around 203 photoelectrons (N pe = ηN γ ) taking into account the maximum quantum efficiency (η = 22% at 390 nm).…”
Section: Incident Photon Yield and Cathode Currentmentioning
confidence: 99%